Identification of Leishmania infantum Epidemiology, Drug Resistance and Pathogenicity Biomarkers with Nanopore Sequencing - Joan Martí-Carreras; Marina Carrasco; Marcel Gómez-Ponce; Marc Noguera-Julián; Roser Fisa; Cristina Riera; Maria Magdalena Alcover; Xavier Roura; Lluís Ferrer; Olga Francino (Microorganisms, 2022)
The emergence of drug-resistant strains of the parasite Leishmania infantum infecting dogs and humans represents an increasing threat. L. infantum genomes are complex and unstable with extensive structural variations, ranging from aneuploidies to multiple copy number variations (CNVs). These CNVs have recently been validated as biomarkers of Leishmania concerning virulence, tissue tropism, and drug resistance. As a proof-of-concept to develop a novel diagnosis platform (LeishGenApp), four L. infantum samples from humans and dogs were nanopore sequenced. Samples were epidemiologically typed within the Mediterranean L. infantum group, identifying members of the JCP5 and non-JCP5 subgroups, using the conserved region (CR) of the maxicircle kinetoplast. Aneuploidies were frequent and heterogenous between samples, yet only chromosome 31 tetrasomy was common between all the samples. A high frequency of aneuploidies was observed for samples with long passage history (MHOM/TN/80/IPT-1), whereas fewer were detected for samples maintained in vivo (MCRI/ES/2006/CATB033). Twenty-two genes were studied to generate a genetic pharmacoresistance profile against miltefosine, allopurinol, trivalent antimonials, amphotericin, and paromomycin. MHOM/TN/80/IPT-1 and MCRI/ES/2006/CATB033 displayed a genetic profile with potential resistance against miltefosine and allopurinol. Meanwhile, MHOM/ES/2016/CATB101 and LCAN/ES/2020/CATB102 were identified as potentially resistant against paromomycin. All four samples displayed a genetic profile for resistance against trivalent antimonials. Overall, this proof-of-concept revealed the potential of nanopore sequencing and LeishGenApp for the determination of epidemiological, drug resistance, and pathogenicity biomarkers in L. infantum.